Direct and Indirect Methods for Studying Human Gut Microbiota - V. T. Ivashkin; O. S. Medvedev; E. A. Poluektova; A. V. Kudryavtseva; I. R. Bakhtogarimov; A. E. Karchevskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: To review the main methods of intestinal microbiota studying.Key points. Currently, molecular genetic methods are used mainly for basic research and do not have a unified protocol for data analysis, which makes it difficult to implement them in clinical practice. Measurement of short chain fatty acids (SCFA) concentrations in plasma provides the data, which can serve as an indirect biomarker of the colonic microbiota composition. However, currently available evidence is insufficient to relate the obtained values (SCFA levels and ratio) to a particular disease with a high degree of certainty. Trimethylamine N-oxide (TMAO) levels in the blood plasma and urine can also reflect the presence of specific bacterial clusters containing genes Cut, CntA/CntB and YeaW/YeaX. Therefore, further studies are required to reveal possible correlations between certain disorders and such parameters as the composition of gut microbiota, dietary patterns and TMAO concentration. Gas biomarkers, i.e. hydrogen, methane and hydrogen sulphide, have been studied in more detail and are better understood as compared to other biomarkers of the gut microbiome composition and functionality. The main advantage of gas biomarkers is that they can be measured multiple times using non-invasive techniques. These measurements provide information on the relative proportion of hydrogenic (i.e. hydrogen producing) and hydrogenotrophic (i.e. methanogenic and sulfate-reducing) microorganisms. In its turn, this opens up the possibility of developing new approaches to correction of individual microbiota components.Conclusions. Integration of the data obtained by gut microbiota studies at the genome, transcriptome and metabolome levels would allow a comprehensive analysis of microbial community function and its interaction with the human organism. This approach may increase our understanding of the pathogenesis of various diseases as well open up new opportunities for prevention and treatment.